2001 Grolier multimedia encyclopedia (Grolier Interactive, 2000)
The 2001 Grolier Multimedia Encyclopedia contains more than 60,000 well-researched articles as well as illustrations, panoramic images, video and sound. These are divided into 5 sections: articles, media, atlas, timelines, and a research starters section, that contains topics for school reports and research.